2016
DOI: 10.1002/smtd.201600006
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured 2D Materials: Prospective Catalysts for Electrochemical CO2 Reduction

Abstract: Electrochemical CO2 reduction to useful fuels and chemicals, driven by renewable energy from intermittent sources such as solar and wind, has been keenly pursued in recent years as a means to resolving energy security and environmental issues associated with conventional fossil fuels. Nanostructured two‐dimensional (2D) materials, possessing abundant active sites in the form of surface atoms and edge sites, and providing better electrical conductivity along 2D conducting channels, represent promising candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 21 publications
1
68
0
Order By: Relevance
“…The ever‐rising demand for fossil fuels and a collateral increase in the concentration of atmospheric CO 2 have urged the development of carbon‐management technologies . To this end, much research has been devoted to searching for new technologies for the reduction of CO 2 , for example biological conversion, electrocatalysis, photocatalysis, and photothermal catalysis . Among them, photocatalytic CO 2 reduction into valuable chemical fuels such as CH 4 , CH 3 OH, HCOOH, and CH 2 O has received great attention because it can alleviate the current dependence on fossil fuels of human society, as well as reducing the CO 2 concentration in the atmosphere .…”
Section: Application Of Direct Z‐scheme Photocatalystsmentioning
confidence: 99%
“…The ever‐rising demand for fossil fuels and a collateral increase in the concentration of atmospheric CO 2 have urged the development of carbon‐management technologies . To this end, much research has been devoted to searching for new technologies for the reduction of CO 2 , for example biological conversion, electrocatalysis, photocatalysis, and photothermal catalysis . Among them, photocatalytic CO 2 reduction into valuable chemical fuels such as CH 4 , CH 3 OH, HCOOH, and CH 2 O has received great attention because it can alleviate the current dependence on fossil fuels of human society, as well as reducing the CO 2 concentration in the atmosphere .…”
Section: Application Of Direct Z‐scheme Photocatalystsmentioning
confidence: 99%
“…Photocatalysis, an advanced catalysis technology that has been widely studied for environmental cleaning and chemical synthesis, has play crucial roles in addressing the global energy and environmental challenges in a sustainable manner. Over the past decade, significant progress has been achieved in the development of 2D materials such as graphene and TMDs as efficient catalysts for photocatalytic H 2 production, water splitting, and CO 2 reduction . Since the advent of MXenes in 2011, they have been predicted as promising cocatalysts for photocatalysis because: i) The surface of the MXenes are terminated by functional groups (‐OH, ‐O, and ‐F) that enable their intimate coupling with other semiconductors for heterostructures.…”
Section: Mxene‐based Catalysts For Photocatalysismentioning
confidence: 99%
“…[18] Compared to 1D nanomaterials, the large-scale synthesis of 2D nanomaterials with well-controlled nanostructures is challenging, as the strongi n-plane bonds, electrostatic interaction, and p-p stacking within the atomic layers often result in severe agglomeration. [19] As for 3D nanomaterials, three-dimensional (3D) nanostructures such as nanodendrites and nanoflowers with trunks,m ultiple side branches, and petals are complex and thus often result in multiple reactionp athways for charge and mass transport. [20] Althoughe xtensive reviews have been reported on 1D materials in different energy storages ystems, such as water-splitting, [18] sodium-ion batteries, [21] Li-ion batteries, [21,22] and fuel cells, [23] nonetheless, the review of applying 1D nanoscale materials for CO 2 RR is still limited.…”
Section: Introductionmentioning
confidence: 99%